Improved Water Use of the Maize Soil–Root–Shoot System under the Integrated Effects of Organic Manure and Plant Density - Li-Chao Wei; Hua-Ping Zhang; Xiao-Lin Wang; Sui-Qi Zhang (Agronomy, 2023)
On the Loess Plateau of China, water shortage and serious soil erosion are the key factors that restrict local agricultural development, especially in terms of crop yield. In order to expound the effect of treatment with organic manure in root growth, water transpiration and evaporation, biomass allocation and grain yield and WUE (water use efficiency), we took maize (Zheng Dan 958) sown for four years with three replicates at three densities. The results show that the highest rate of maize grain yield increase with organic manure is about 9.99% for a density of 90,000 plants/ha; at the same time, ET (evapotranspiration) and WUE also achieved marked increments, which the highest values of 415.47 mm with a density of 75,000 plants/ha and 7.92% with a density of 90,000 plants/ha, respectively. The results also demonstrate the obvious effect of organic manure in enhancing root growth and in the maximization of water transpiration and evaporation, and water use plays a vital and valuable role in biomass allocation. The results also serve as orientation for methods to increase maize yield and a reference for other crops in the relation of water and manure to their growth.